THE CHOICE OF AN INDEPENDENT CENTRAL LOGISTICS DEPARTMENT IN A MANUFACTURING COMPANY (Perner's Contacts, 2015)
In preparation for the broader topic structure of logistics processes was research done. The research question was, if the choice of an independent central logistics department in a manufacturing company is in relation with the size of the manufacturing company or branch. The aim of this paper is to present some results of this research.
Keywords: logistics, logistics process, logistics design